2016
DOI: 10.4103/0976-7800.191015
|View full text |Cite
|
Sign up to set email alerts
|

Severely calcified leiomyoma of broad ligament in a postmenopausal woman: Report of a rare case

Abstract: Calcified broad ligament leiomyoma is a rare benign lesion in postmenopausal age group. It causes diagnostic confusion with solid calcified adnexal mass and large bladder calculi at the pelvic region. Clinical and radiological diagnoses were confirmed by histopathology of the hysterectomy specimen. We hereby present a case of heavily calcified broad ligament fibroid in a postmenopausal woman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Although rare, anecdotal cases of huge fibroids in postmenopausal women have been reported in the literature previously [ 6 , 7 ]. Their occurrence after menopause could be due to stimulation of the growth by estrone, insulin-like growth factor, or epidermal growth factor [ 8 ]. In postmenopausal women with obesity, peripheral aromatization of adrenal-derived androstenedione into estrone might be responsible for the increase in size.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although rare, anecdotal cases of huge fibroids in postmenopausal women have been reported in the literature previously [ 6 , 7 ]. Their occurrence after menopause could be due to stimulation of the growth by estrone, insulin-like growth factor, or epidermal growth factor [ 8 ]. In postmenopausal women with obesity, peripheral aromatization of adrenal-derived androstenedione into estrone might be responsible for the increase in size.…”
Section: Discussionmentioning
confidence: 99%
“…Shrestha et al published a case of a menopausal woman who presented with acute abdomen due to fibroid degeneration [9]. Another case of a calcified fibroid was reported in a postmenopausal woman, managed with hysterectomy [8]. Myomectomy or hysterectomy must be planned depending on the patient's age, type and size of the fibroid, severity of symptoms, desire to conceive in the future, suspicion of malignancy, and proximity to menopause [6].…”
Section: Discussionmentioning
confidence: 99%
“…When the myoma grows rapidly and blood supply is insufficient, various degenerative changes occur. 26 A review of the literature showed that the uterus, the tumor corresponds to a broad ligament leiomyoma. 3,27 Ultrasound in most reported cases of the literature review showed heterogeneous mass with multiple septations.…”
Section: Discussionmentioning
confidence: 99%
“…All clinical data identified in the literature review are listed in Table 1, and the proportions of clinical symptoms are listed in Table 2. When the myoma grows rapidly and blood supply is insufficient, various degenerative changes occur 26 . A review of the literature showed that 47.62% of giant broad ligament leiomyomas exhibited degeneration, of which cystic degeneration was the most common, with an incidence of 38.1% (8/21), and myxoid degeneration accounted for 19.1% (4/21).…”
Section: Discussionmentioning
confidence: 99%
“…The large broad ligament myoma often complicates with degeneration due to its large volume, which leads to the relative lack of blood supply inner the leiomyoma. The commonly seen degeneration types include hyaline degen- eration (63%), myxomatous degeneration (13%), calcified degeneration (8%), mucoid degeneration (6%), cystic degeneration (4%), red degeneration (3%), and fatty degeneration (3%) [6], which bring some difficulty in imaging diagnosis. In this case, according to the results of ultrasound and enhanced CT, the tumor was considered from the right adnexal area or giant broad ligament, and the nature of the tumor remained unknown.…”
Section: Discussionmentioning
confidence: 99%